2018
DOI: 10.24996/ijs.2018.59.4c.5
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Shows Independency form Hemolysin Genes Arsenal in Methicillin Resistant Staphylococcus Aureus

Abstract: Normally, bacteria exposed to antibiotics at sub minimal inhibitory concentrations (MIC) inside the host. Therefore, the current study aimed to comprehend the association among hemolysins, biofilm, as well as gentamicin resistance in local MRSA isolates. Around 35 Staphylococcus aureus locally isolated from different clinical specimens were employed in this study. Methicillin resistance was detected via cefoxitin disk diffusion and mecA amplification methods. MIC of gentamicin was estimated by broth microdilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Assessing biofilm formation of P. aeruginosa isolates Isolates of Pseudomonas aeruginosa may be able to develop biofilms on microtiter plates (Table 8). The results suggested that P. aeruginosa (40.0%) isolates produced strong biofilms, while 33.3 and 26.6% of isolates produced moderate and weak biofilms, respectively [30][31][32][33].…”
Section: Anti-biofilm (Biological Activity)mentioning
confidence: 98%
“…Assessing biofilm formation of P. aeruginosa isolates Isolates of Pseudomonas aeruginosa may be able to develop biofilms on microtiter plates (Table 8). The results suggested that P. aeruginosa (40.0%) isolates produced strong biofilms, while 33.3 and 26.6% of isolates produced moderate and weak biofilms, respectively [30][31][32][33].…”
Section: Anti-biofilm (Biological Activity)mentioning
confidence: 98%